Das Gebet im Neuen Testament Vierte europäische orthodox-westliche Exegetenkonferenz in Sambata de Sus, 4.-8. August 2007 - Niebuhr, Karl-Wilhelm; Karakolis, Christos; Klein, Hans; Mihoc, Vasile (Mohr Siebeck, 2009)
Prayer in the New Testament. Fourth European Orthodox-Western Conference of Exegetes in Sambata de Sus from August 4-8, 2007
PublicationDate: 20100111
Keywords: Hermeneutik -- Ökumene -- Gebet -- Liturgie -- Neues Testament -- Array